Voltammetric sensor for simultaneous determination of p-phenylenediamine and resorcinol in permanent hair dyeing and tap water by composite carbon nanotubes/chitosan modified electrode - Hudari, Felipe Fantinato [UNESP]; Almeida, Lucio Cesar de [UNESP]; Silva, Bianca Ferreira da [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier B.V., 2014)
p-Phenylenediamine (PPD) and resorcinol (RSN) are hair dye precursors of permanent dyeing more used worldwide. The present work describes a simple and economic voltammetric sensor for simultaneous determination of both components in commercial hair dyeing and tap water at low concentrations. PPD and RSN are oxidized at + 0.17 and + 0.61 V vs. Ag/AgCl at glassy carbon electrode coated by composites of multiwall carbon nanotubes with chitosan (MWNTs-CHT/GCE), which anodic currents density normalized are 10% and 70% higher in relation to the unmodified electrode, respectively. The calibration curve for simultaneous determination of PPD and RSN showed linearity between 0.55 and 21.2 mg L-1 with detection limits of 0.79 and 0.58 mg L-1 to PPD and RSN, respectively. The relative standard deviations found for ten determinations were of 0.73 and 2.35% to 2.70 mg L-1, and 0.87 and 1.08% to 15.96 mg L-1 to PPD and RSN, respectively. The voltammetric sensor was applied to determination of PPD and RSN in tap water and commercial hair dyeing samples and the average recovery for these samples was around 97%. The products generated from PPD and RSN reaction such as was p-quinonediimine and bandrowski base were detected by LC-MS/MS and UV-vis spectrophotometry. (C) 2014 Published by Elsevier B.V.
Keywords: p-Phenylenediamine; Resorcinol; Modified glassy carbon electrode; Hair dye